Beneficial autoimmunity and maladaptive inflammation shape epidemiological links between cancer and immune-inflammatory diseases. (31st December 2022) - Pol, Jonathan; Paillet, Juliette; Plantureux, Céleste; Kroemer, Guido
ABSTRACT: Chronic inflammation drives proliferative responses, hence increasing cellular multiplication with the consequent risk of malignant transformation. Autoimmune responses against self-antigens drive chronic inflammation but may also enhance cancer immunosurveillance with the consequent reduction of tumor incidence and progression. These notions, which have been well established at the preclinical level, may explain the generally positive associations between immune-inflammatory diseases but also some negative associations, for example between breast cancer and rheumatoid arthritis or systemic lupus erythematosus, which have recently been confirmed in a study enrolling close to half a million participants from the UK Biobank.